Altered Venous Function during Long-Duration Spaceflights - Fortrat, Jacques-Olivier; de Holanda, Ana; Zuj, Kathryn; Gauquelin-Koch, Guillemette; Gharib, Claude (Frontiers in Physiology, 2017)
Aims: Venous adaptation to microgravity, associated with cardiovascular deconditioning, may contribute to orthostatic intolerance following spaceflight. The aim of this study was to analyze the main parameters of venous hemodynamics with long-duration spaceflight. Methods: Venous plethysmography was performed on 24 cosmonauts before, during, and after spaceflights aboard the International Space Station. Venous plethysmography assessed venous filling and emptying functions as well as microvascular filtration, in response to different levels of venous occlusion pressure. Calf volume was assessed using calf circumference measurements. Results: Calf volume decreased during spaceflight from 2.3±0.3 L to 1.7±0.2 L (p<0.001), and recovered after it (2.3± 0.3 L). Venous compliance, determined as the relationship between occlusion pressure and the change in venous volume, increased during spaceflight from 0.090±0.005 to 0.120±0.007 (p<0.01) and recovered 8 days after landing (0.071±0.005, arbitrary units). The index of venous emptying rate decreased during spaceflight from -0.004±0.022 to -0.212±0.033 (p<0.001, arbitrary units). The index of vascular microfiltration increased during spaceflight from 6.1±1.8 to 10.6±7.9 (p<0.05, arbitrary units). Conclusion: This study demonstrated that overall venous function is changed during spaceflight. In future, venous function should be considered when developing countermeasures to prevent cardiovascular deconditioning and orthostatic intolerance with long-duration spaceflight.